PENGGUNAAN METODE DISCOVERY LEARNING PADA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA DI SMA AL-HIDAYAH MEDAN JLN. LETDASUJONO T.A 2021/2022 - Zulkarnaen Guchi, Rizki Asiyah, Mohammad Firman Maulana (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
Discovery Learning is a learning theory that is defined as a learning process that occurs when lessons are not presented with learning in its final form, but students are expected to organize themselves. By using the Discovery Learning method, it means that the teacher provides an introduction and keywords of the material being taught and students are actively guided to discover what they are learning. This study aims to improve the learning achievement of Islamic Religious Education students of class X SMA Al-Hidayah Medan in the even semester of the 2021/2022 academic year by using the discovery learning method on honesty material as a mirror of personality. This type of research is qualitative research, namely the research method used to examine the condition of natural objects, where the researcher is the key instrument. Student responses to the application of discovery learning methods in Islamic Religious Education learning and student learning outcomes in Islamic Religious Education learning using the discovery learning method can improve learning outcomes very well. Based on the results of the research and discussion of the research, it can be concluded that through the application of the discovery learning model can improve the learning achievement of Islamic Religious Education students with honesty material as a mirror of personality in class X SMA Al-Hidayah.